Discrete mathematics and its applications - Rosen, Kenneth H.; Krithivasan, Kamala (New York : McGraw-Hill, 2013)
Intends to meet the needs of international students of discrete mathematics. This title covers chapters such as: Boolean Algebra and Modeling Computation; and, revised problems for the international student integrating alternative methods and solutions.
1. The foundations: logic and proofs -- 2. Basic structures: sets, functions, sequences, sums, and matrices -- 3. Algorithms -- 4. Number theory and cryptography -- 5. Induction and recursion -- 6. Counting -- 7. Discrete probability -- 8. Advanced counting techniques -- 9. Relations -- 10. Graphs -- 11. Trees -- 12. Algebraic structures and coding theory
Global edition
Includes bibliographical references and index
Keywords: Computer science -- Mathematics; Mathematics